Integration of Qur'an and Hadith Values as Pedagogical Innovation to Improve the Quality of Islamic Education - Sugiarto, Fitrah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze the integration of Qur'anic and Hadith values into learning methodologies to enhance the quality of Islamic education. This research employs a qualitative approach with a literature study method, utilizing primary sources from the Qur'an and Hadith and secondary sources from books, journal articles, and other scholarly references on Islamic pedagogy. Data was collected through document analysis, identifying relevant texts discussing Islamic educational principles and their applications in contemporary learning frameworks. The data were analyzed using content analysis, focusing on extracting key educational themes from Qur'anic and Hadith texts and their alignment with modern pedagogical approaches. The findings reveal that Islamic educational principles, including tarbiyah (holistic education), ta’lim (knowledge transmission), and ta’dib (character formation), can be effectively implemented through various innovative teaching strategies. These include project-based learning, technology-assisted instruction, and participatory methods emphasizing dialogue, critical thinking, and experiential learning. Such approaches ensure that Islamic education remains rooted in traditional values while adapting to contemporary educational needs. The study further finds that integrating Qur'anic and Hadith-based innovations enhances students’ motivation, critical thinking skills, and ability to balance faith with scientific knowledge. These pedagogical transformations contribute to developing a dynamic and sustainable Islamic education system that is contextually relevant and future-oriented.